A new Changhsingian brachiopod fauna from the Xiala Formation at Tsochen in the central Lhasa Block and its paleogeographical implications - Xu, Hai-Peng; Zhang, Yi-Chun; Qiao, Feng; Shen, Shu-Zong (Journal of paleontology, 2019)
Permian faunal affinity in the Lhasa Block plays a critical role in reconstructing its paleogeographic evolution. Cisuralian and Guadalupian faunas have been described from the Lhasa Block, but very few Lopingian (late Permian) brachiopods have been reported so far. In this paper, a new diverse brachiopod fauna consisting of 17 species of 17 genera and an unidentifiable Orthotetoidea is described from the uppermost part of the Xiala Formation at the Aduogabu section in the central part of the Lhasa Block. The age of this fauna can be assigned to the Changhsingian (late Lopingian) as indicated by the associated foraminifers Colaniella parva (Colani, 1924) and Reichelina pulchra Miklukho-Maklay, 1954. Characteristic brachiopods include Spinomarginifera chengyaoyenensis Huang, 1932, Haydenella wenganensis (Huang, 1932), and Araxathyris cf. dilatatus Shen, He, and Zhu, 1992. They also generally suggest a Changhsingian age. Paleobiogeographically, this fauna is uniformly composed of typical Tethyan elements represented by Spinomarginifera Huang, 1932 and Haydenella Reed, 1944, and some cosmopolitan elements, but no typical cold-water taxa of Gondwanan affinity. This is in contrast to the contemporaneous brachiopod faunas from the Tethys Himalayan region that are characterized by typical cold-water taxa of Gondwanan affinity, e.g., Costiferina indica (Waagen, 1884), Retimarginifera xizangensis Shen et al., 2000, Neospirifer (Quadrospina) tibetensis Ding, 1962. Thus, it is strongly indicative that the Lhasa Block had drifted into a relatively warm-water regime during the Changhsingian. An analysis of the paleobiogeographic change of brachiopods in the Lhasa Block throughout the entire Permian further suggests that the Lhasa Block probably had rifted away from the northern peri-Gondwanan margin between the latest Cisuralian and middle Guadalupian, that is, the Neotethys Ocean had opened before middle Guadalupian.